Beginnings of the Cold War arms race : the Truman administration and the U.S. arms build-up - Ojserkis, Raymond P., 1969- (Praeger, 2003)
The Truman administration's decision to embark on an arms build-up in 1950 was a critical event. For the first time other than a World War, the United States became a global military presence. Unlike the World Wars, in this instance the deployment lasted decades, altering the nature of the Cold War and the United States' global role. Such a decision deserves a book dedicated to understanding the strategy and politics behind it. The Beginnings of the Cold War Arms Race serves that purpose.